Edukasi Akupresure Mandiri Untuk Mengatasi Low Back Pain Pada Ibu Hamil TM III - Asirotul Ma’rifah; Naning Puji Suryantini (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2023)
Many pregnant women think lower back pain is not something to worry about, but in fact if it is not treated well and early, the prognosis for lower back pain will be poor. Usually pregnant women with lower back pain will have difficulty carrying out activities, for example difficulty getting into a position from sitting to standing, and vice versa, mothers will even have difficulty getting out of bed. Various complementary techniques, including acupressure, have been researched and developed to treat lower back pain in pregnant women (Purnamasari, 2019). Acupressure is part of physiotherapy where this technique is given with massage and stimulation focused on certain points on the body, so that the aches and pains felt will be reduced and the circulation of vital energy and chi will be active again. The aim of this community service is to educate pregnant women on how to do acupressure independently to treat lower back pain. Implementation method: Consists of preparation stage, implementation stage and reporting. There were 16 respondents from third trimester pregnant women in Kemsantani Village, Gondang, Mojokerto. The results show that 11 people (69%) experienced an increase in knowledge after comparing the knowledge scores before and after implementing community service activities. In this community service activity, pregnant women can carry out acupressure techniques well independently.